Exploring the Use of Virtual Reality for the Delivery and Practice of Stress-Management Exercises - Soh, Desmond Jun Hong; Ong, Crystal Huiyi; Fan, Qianqian; Seah, Denise Ju Ling; Henderson, Stacey Lee; Jeevanandam, Lohsnah; Doshi, Kinjal (Frontiers in Psychology, 2021)
Background: Mindfulness-based interventions may benefit healthcare professionals with burnout symptoms. Virtual reality (VR) may reduce initial difficulty of engaging in mindfulness exercises and increase participants’ engagement through immersion and presence. Aim: The aim was to investigate how VR affects participants’ experience of engagement with mindfulness practice, and its impact on quality of practice and negative mood states. Methods: 51 healthcare professionals were randomized to receive either a visualization or non-visualization mindfulness practice, to compare the quality of practice through the use of audio only versus with a virtual reality interface. Selected self-reported measures were collected during the session (immersion, quality and difficulty of practice, mood states and likelihood for future practice). Results: Results showed that type and order of modality administered made a difference in quality of mindfulness practice. Participants were more receptive to VR (F = 3.827, p = 0.056, Partial η2 = 0.072). A greater sense of presence was reported with VR if administered after audio (F = 4.810, p = 0.033, Partial η2 = 0.093). Further, participants described difficulty practicing with audio if administered after VR (F = 4.136, p =0.048, Partial η2 = 0.081). Additionally, lower mood disturbance was reported with VR if administered after audio (F = 8.116, p = 0.006, Partial η2 = 0.147). Qualitative responses echoed a preference for VR to engage better, in addition to improved mood states after practice. Conclusion: Findings suggest that VR has the potential to provide healthcare professionals with an alternative or a supplement to conventional mindfulness practice.